Extended reality (XR) in psychosocial and forensic interventions for child and adolescent sexual abuse: a systematic review of current applications and future directions - Leiva, Varinia; Pereda, Noemí; Cenzano, Nicolás (Frontiers in Psychology, 2025)
The integration of extended reality (XR) technologies—virtual (VR) and augmented (AR)—into child sexual abuse (CSA) interventions has grown over the past decade. This systematic review explores the application, efficacy, and ethical implications of XR tools in psychosocial, forensic, preventive, and therapeutic approaches addressing CSA. Following PRISMA guidelines, a comprehensive search was conducted across Scopus, Web of Science, and PubMed, identifying 11 empirical studies published between 2014 and 2024. Three main intervention categories emerged: (1) professional training, (2) prevention, and (3) therapeutic treatment. Most studies focused on enhancing forensic interviewing skills through avatar-based simulations and immersive training, demonstrating increased use of relevant questions and improved self-efficacy among professionals. Preventive interventions used VR and serious games in school settings to promote body safety awareness and protective behaviors in children. Despite their promise, only one study addressed therapeutic applications directly, highlighting the use of a nonverbal digital tool and serious game to facilitate trauma narration in children with CSA experiences, based on trauma-focused cognitive-behavioral therapy (TF-CBT). The findings emphasize XR's potential to foster engagement, realism, and emotional safety in highly sensitive contexts, specifically in CSA interventions. However, challenges include limited longitudinal evidence, lack of culturally diverse studies, and ethical concerns about exposure, re-victimization, and emotional risks for minors. This review underscores the need for more ethically rigorous research to determine the impact of XR-based interventions in child sexual victimization management.